FACTORS THAT INFLUENCE BATAM STUDENTS' INTEREST IN INVENTING IN THE CAPITAL MARKET - Efriyenti, Dian; Azmiana, Risca; Tobing , Vargo Christian L.; Rustam, Triana Ananda (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
Many prospective investors, including students, feel hesitant to invest due to a lack of understanding of financial literacy. This is exacerbated by previous experiences of losses that make them even more hesitant in making investment decisions. In addition, the assumption that the minimum capital required to invest is very large is also a factor that inhibits investment intentions. The method used in this study is quantitative, with a research population of 100 accounting study program students in Batam City. To determine a representative sample, the researcher used the Slovin formula, which resulted in 97 respondents. The sampling technique applied was simple random sampling, so that each individual had an equal opportunity to be selected. Data collection was carried out by distributing questionnaires that had been tested for validity and reliability. Furthermore, data analysis was carried out using multiple linear regression tests. The results of the analysis showed that minimum capital had a significant effect on the investment interest of accounting students in Batam, while financial literacy had an effect but was not significant. Based on the results of simultaneous testing in this study, it can be concluded that the independent variables (minimum capital and financial literacy) have a simultaneous effect on the interest of accounting students